Overcoming multifaceted challenges in cancer treatment: Targeting signal transduction pathways and tumor microenvironment for enhanced therapeutic efficacy - Abdul Majeed Ansari, Naresh Kumar Sharma, Kashinath Tripathi, Gautam Bhardwaj, Ritu Chauhan, Rajiv Kumar Tonk, Moyad Shahwan, Hardeep Singh Tuli, Abhishek Chauhan (Journal of Applied Pharmaceutical Science, 2025)
Cancer, a leading global cause of mortality, persists despite extensive research. While progress, notably in protein kinase-modulating drugs, is evident, a definitive cure remains elusive due to multifaceted challenges. This article discusses diverse approaches in cancer treatment, recognizing its complexity. Key hurdles include cancer progression stages, the intricate tumor microenvironment, drug resistance, pharmacodynamics, tumor hypoxia, and compromised immunity. Signal transduction pathways are crucial in cancer progression and resistance, particularly in immune regulation, hypoxia response, and autophagy. Understanding and targeting these pathways are vital for developing novel therapies. By elucidating the interplay between immunity, signaling, and therapeutics, researchers seek to overcome treatment obstacles. A comprehensive approach offers hope for improved outcomes and breakthroughs in cancer management.
Keywords: Autophagy, drug resistance, hypoxia, immune regulation, signal transduction, tumor microenvironment